User Experience Sistem Metaverse Tata Surya Berbasis Platform Spatial.io Menggunakan Metode UEQ - Hidayati, Awanis; Nusantara, Novaria; Susanty, Arie; Wicaksono, Adjie (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
The integration of Metaverse technology into vocational education introduces an immersive and contextual approach to learning. This study evaluates the quality of User Experience in a Solar System learning system developed on the Spatial.io platform, implemented for Grade XI students majoring in Computer and Network Engineering at SMK Immanuel Pontianak. The evaluation was conducted using the User Experience Questionnaire (UEQ), which assesses six core dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The analysis revealed positive scores across all dimensions, with the highest ratings in Stimulation (1.99) and Attractiveness (1.90), and the lowest in Dependability (1.23), which nonetheless remained within the favorable range. Reliability testing resulted in Cronbach’s Alpha values above 0.70 for all dimensions, indicating strong internal consistency and trustworthy measurements of User Experience. These findings suggest that the Spatial.io-based learning system is both adaptive and engaging as a digital learning medium. Future development opportunities include improving system precision and content novelty, as well as expanding implementation across different topics and educational levels. The results of this study are expected to contribute to the advancement of Metaverse-based learning systems within the field of Informatics, with a focus on user-centered design and experience.